Effect of cumin and coriander seeds consumption on dyslipidemia, abdominal fat, body weight, and lipid profile in rat models : Cumin and coriander seeds consumption and dyslipidemia - Iqbal, Sehar; Saeed, Rida Fatima; Zafar, Saira; Qazi, Asma Saleem; Shah, Syed Hassan Bin Usman; Abid, Juweria; Farooq, Umar; Akram, Sajeela; Ahmad, Abdul Momin Rizwan (Cellular and Molecular Biology, 2025)
Dyslipidemia is considered a crucial risk factor for high risk of atherosclerosis and cardiovascular diseases. Cumin and coriander seeds are well-known flavoring agents that contain nutraceutical properties and appear to have beneficial health effects. A study was therefore conducted to investigate the effects of cumin and coriander seeds on body weight, abdominal fat and lipid profile in rats. For this purpose, 18 male albino rats were fed on fat-rich diet (diet A) for 14 days, followed by the control diet mixed separately with 20 g of cumin (diet B) and 20g of coriander (diet C) for the next 4 weeks. The body weights and lipid profiles of the rats were analyzed at the start of the intervention and thereafter weekly. Results showed that cumin seeds help to reduce body weight, ranging from 178g to 141g (37g), even for a short time. Post-mortem examination revealed that rats fed cumin diet have less fat accumulation in abdominal cavity compared to control and coriander seeds diets. Elevated values of high-density lipoprotein (HDL) were observed particularly from day 14 to 35 in rats fed with both cumin (from 72.3 to 88.0 mg/dl) and coriander seeds, (from 63.2 to 88.0 mg/dl) as compared to control group (55.0 mg/dl) (P>0.05). Also, a remarkable reduction of low-density lipoprotein (LDL) and total lipid profile was seen in cumin group, as compared to the controls. This interventional study reported that cumin seeds helped in the significant reduction of weight, abdominal fat and total lipid profile while increasing the HDL in rats.